Prediction of antipsychotics efficacy based on a polygenic risk score: a real-world cohort study - De Pieri, Marco; Ferrari, Marco; Pistis, Giorgio; Gamma, Franziska; Marino, Franca; Von Gunten, Armin; Conus, Philippe; Cosentino, Marco; Eap, Chin-Bin (Frontiers in Pharmacology, 2024)
Response to antipsychotics is subject to a wide interindividual variability, due to genetic and nongenetic factors. Several single nucleotide polymorphisms (SNPs) have been associated with response to antipsychotics in genome-wide association studies (GWAS). Polygenic risk scores (PRS) are a powerful tool to aggregate into a single measure the small effects of multiple risk alleles.We studied the association between a PRS composed of SNPs associated with response to antipsychotics in GWAS studies (PRSresponse) in a real-world sample of patients (N=460) with different diagnoses (schizophrenia spectrum, bipolar, depressive, neurocognitive, substance use disorders and miscellaneous). Two other PRSs composed of SNPs previously associated with risk of schizophrenia (PRSschizophrenia1 and PRSschizophrenia2) were also tested for their association with response to treatment.PRSresponse was significantly associated with response to antipsychotics considering the whole cohort (OR=1.14, CI=1.03-1.26, P=0.010), the subgroup of patients with schizophrenia, schizoaffective disorder or bipolar disorder (OR=1.